Tinjauan Yuridis terhadap Penyebaran Data Pribadi yang Dilakukan oleh Aplikasi Pinjaman Online Ilegal - Masriyani, Masriyani; Siregar, Nella Octaviany; Tresya, Tresya (Universitas Batanghari Jambi, 2024)
Information technology impacts social, cultural, and economic progress, creating a world that is not limited by time, geography, or distance. Fintech, short for financial technology, is a phrase used to describe technology that facilitates communication between society and society's financial sector. In Indonesia, protecting personal information is a primary concern. This is due to the increasing volume of digital activity, especially transactions involving the submission of personal data by users. A normative approach was used in carrying out this research. This study focuses on the legal or statutory approach. Qualitative analysis is a type of data analysis used in normative legal studies. The latest legal regulations regarding efforts to safeguard personal data, especially related to criminal acts that occur and are carried out by unauthorized pinjol applications, are Law Number 27 of 2022 concerning Personal Data Protection. The PDP Law serves as a foundation and ensures that everyone's personal information is legally protected, preventing misuse of personal information for purposes that could harm third parties. In addition, the PDP Law provides administrative and criminal sanctions for all crimes related to personal data, including misuse of data and unauthorized access to that data, such as in cases of illegal online loan applications.